Accountability frameworks for Indigenous financial institutions in Australia, Canada, and New Zealand - Henry, Ella; Poyser, Andre; Schneider, Bettina (Journal of Aboriginal Economic Development)

(untitled) (CANDO, 2025)
Indigenous peoples around the world share a history of colonization and poverty, including the loss of land, language, and the cultural foundations of their societies and communities. An increasing number of Indigenous peoples are actively rebuilding and revitalizing their cultures through economic endeavour. This paper presents case studies from Australia, Canada, and New Zealand, highlighting applicable models of collaborative co-governance employed by Indigenous finance entities, as well as the accountability frameworks that have emerged from this renaissance. We found evidence of commonalities based on the cultural values and traditional knowledge systems of Indigenous peoples in their respective countries. The literature informs our analyses, as it originates from our organizations and communities of interest. We discovered that, despite the social, cultural, and economic differences, the exciting and innovative strategies developed by Indigenous peoples in all three countries are not only similar and relevant to one another but also applicable to non-Indigenous financial and investment institutions and their accountability frameworks. The integration of Indigenous philosophies and values into the governance of Indigenous financial and investment entities has fostered a multi-dimensional approach that considers both Western and Indigenous practices. The necessity of meeting both Indigenous and non-Indigenous accountability requirements creates an interlocking circle of values and codes of conduct, providing Indigenous financial and investment entities with a double layer of protection.